Hubungan Antara Status Gizi Dan Perilaku Hidup Bersih Dan Sehat Dengan Kejadian Diare Pada Balita Usia 12 - 24 Bulan Di Wilayah Puskesmas Colomadu 1 Kabupaten Karanganyar - PROBOWATI, DEVI (2016)
Background : The prevalence of diarrhea in toddlers at Central Java as much as 5.4%. The prevalence of diarrhea in 12-24 months toddlers at Colomadu 1 Primary Health Service, Karanganyar of the months October 2014-January 2015 as much as 22%.Diarrhea in infants is due to several factors: poor nutrition status and PHBS unfavorable. Objective : To determine the relationship of nutritional status and healthy hygiene behaviorsto incidence of diarrhea in 12-24 monthstoddlers at primary health service, Karanganyar. Research Method : This is a cross sectional study conducted at the integrated service center in Primary Health Service Colomadu 1. In total,45 respondents, were surveyed using simple random sampling. The research instruments were a questionnaires incidence of diarrhea and healthy hygiene behaviors. Analysis Techniques used Rank Spearman's test. Results : The respondents have no diarrhea status of 91.1%. Of respondents had good not status and 97.8%. Have good PHBS 86.7%. Toddlers with good nutritional status and no was diarrhea 87.7%, while and toddlers who has malnutrition 50%. Mothers with good PHBS has toddlers no diarrhea is 84.4% while mothers with normal and PHBS has no diarrhea is 2.2%. Conclusion : There was norelationship between nutritional status with incidence of diarrhea in toddlers aged 12-24 months and there was norelationship between healthy hygiene behaviors with incidence of diarrhea in toddlers aged 12-24 months. Therefore, it is suggested that health professionals further improve supervision and counseling about diarrhea and healthy hygiene behaviors in the public. Keywords :Toddler, Nutritional Status, Healthy Hygiene Behaviors, Incident of Diarrhea Kepustakaan : 72 :1999-2014